Detecting Presence of Power Law to Understand the Distribution of Patient Groups Related to Chronic Diseases on Social Media - M. Sridevi,B.R. ArunKumar (International Journal of Advanced Science and Technology, 2020)
Social networking has opened up new research avenues in diversified domains and healthcare is one among them. Interactions on online social networks may result in discussions on health and healthcare related issues that enable the participants to share their experiences in dealing with the disease. This is especially useful in the scenario of chronic diseases where the disease persists with various stages of progression having different symptoms, diagnosis and treatment. Even the lifestyle parameters affect the onset and progression of chronic diseases. In this context, healthcare consumers tend to use social networking as a tool to share their experiences for emotional and informational support that would help to overcome geographical barriers and come together as a group. Our present study attempts to analyse the distribution of patient groups of two chronic diseases namely Alzheimer’s and Diabetes on Facebook, their compliance with power law distribution that is inherent characteristic of real-world networks, trends of creation of these groups over the last decade and their current activity status. The outcomes of our research provides a good foundation for further study on the usage of social networking in healthcare and allied sectors.